VD_FINDINFO Pron / 2013 / 54 vom 10. Januar 2013 - VD Tribunal cantonal (2013)
CURATELLE DE GESTION, CURATELLE DE REPRÉSENTATION, PROCÈS DEVENU SANS OBJET | 400 CC, 450 CC, 450d al. 2 CC, 242 CPC (CH)